Grey matter volume reduction and its association with brain-enriched blood biomarkers in out-of-hospital cardiac arrest survivors - Hollmén, Carita C.; Vorobyev, Victor; Parkkola, Riitta; Posti, Jussi P.; Saunavaara, Jani; Laitio, Ruut; Arola, Olli; Hynninen, Marja; Bäcklund, Minna; Blennow, Kaj; Zetterberg, Henrik; Martola, Juha; et al. (Springer Nature, 2026)
Elevated levels of blood-based biomarkers such as neurofilament light chain (NfL) and neuron-specific enolase (NSE) are associated with poor neurological outcome after out-of-hospital cardiac arrest (OHCA). This study investigates the relationship between regional grey matter volume reduction and levels of glial fibrillary acidic protein (GFAP), NfL, NSE, and total-tau (t-tau) protein. This substudy of the Xe-Hypotheca trial included 110 patients randomized to receive either inhaled xenon with target temperature management (TTM) at 33 °C for 24 h (n = 55) or TTM alone (n = 55). Voxel-based morphometry was used to assess grey matter volume changes in MRI scans acquired 36–52 h and 10 days after OHCA in 45 survivors. Blood biomarkers were measured upon intensive care unit arrival and at 24, 48 and 72 h post-OHCA. NfL levels positively correlated with grey matter volume reduction in the thalamus and cingulate cortex at 24 h post-OHCA. T-tau showed more extensive pattern of significant correlations, increasing in both magnitude and spatial extent from baseline to 48 h post-OHCA. No significant biomarker–volume associations were observed for GFAP or NSE, and no treatment group differences were detected. Elevated NfL and t-tau levels were associated with region-specific grey matter volume reduction within the first 10 days after OHCA. Among the four biomarkers studied, t-tau demonstrated the strongest and most widespread associations, suggesting its potential as a marker for early ischemic grey matter volume reduction after OHCA. ClinicalTrials.gov NCT00879892, 13/04/2009.